The role of microstructure on the mechanical properties of polyurethane foams containing thermoregulating microcapsules. (July 2017) - Serrano, Angel; Borreguero, Ana M.; Garrido, Ignacio; Rodríguez, Juan F.; Carmona, Manuel
Abstract: Rigid polyurethane foams with up to 50 wt% of microcapsules from LDPE-EVA containing Rubitherm ® RT27 were synthesized. The influence of microcapsules on the foams density, microstructure and mechanical resistance was studied. Cell size and strut and wall thicknesses were analyzed by SEM. The relationships between densities and foam microstructures with their Young's moduli and collapse stress were found by the Gibson and Ashby formulations and the Kerner equation for mechanical properties of composites. It was found a cell structure change from polyhedral closed-cells to spherical or amorphous open-cells. A good agreement between the experimental and theoretical data was observed but requiring a cell form factor. Thus, Fitting parameters confirmed the high trend of these microcapsules to be incorporated into the foam cell walls and the form factors depicted the abrupt change of cell morphology. Thus, these equations are suitable for predicting the mechanical properties of foams containing fillers of low mechanical resistance.